Preliminary results of a study of N'Dama cattle introduced in a metayage system in Idiofa District, Zaire - Winckel, F. van; D'Ieteren, G.D.M.; Leak, S.G.A.; Maehl, J.H.H.; Minengu, M.; Nagda, S.M.; Ngamuna, S.; Rarieya, J.M.; Rowlands, G.J.; Thorpe, W.R.; Trail, J.C.M. (OAU/STRC, 1991)
Presents preliminary results of a study of N'Dama cattle introduced in a metayage system in Zaire. Studies tsetse relative densities, tsetse challenge, corrected tsetse challenge, trypanosome prevalence and PCV in gallery forest, savanna woodland and grass savanna areas. Also presents data on feeding preferences of G. fuscipes by different animals and illustrates the effects of trypanosome infections in the dam and in the calf on weight of calf.